Pioneer Rocketry - 2022 Collegiate Rocket Launch Competition - Hornung, Alexander; De La Cruz, Bella; Taylor, Joey; Detrie, Matthew; Borck, Steven (Proceedings of the Wisconsin Space Conference, 2023)
The Wisconsin Space Grant Consortium hosts the annual Collegiate Rocket Launch Competition every year. The goal of the competition this year was to design and build a rocket that can achieve an apogee below 3500 ft, has a system that can stabilize the roll-rate after motor burnout, has a system that logs the acceleration and roll of the flight, and utilizes a dual-deploy recovery system. The rocket, Sialia, used a I435 motor to lift off to an apogee of 1970 ft and successfully recovered using a dual-deploy system. Unfortunately, neither the control system nor the flight recording systems were confirmed to function due to the camera system and Sialia landing in water. Pioneer Rocketry is very proud to have placed second in this competition.